(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article explores the pivotal role of social media advertising in contemporary marketing strategies, focusing on its effectiveness in reaching and engaging target audiences. By analyzing the dynamic landscape of social media platforms, consumer behavior trends, and successful case studies, this study highlights the multifaceted impact of social media advertising. Employing a mixed-methods approach involving quantitative data analysis and qualitative content analysis, the article provides insights into the strategies that optimize audience reach and engagement, contributing to a deeper understanding of the evolving marketing paradigm.